Mg‐CS/HA Microscaffolds Display Excellent Biodegradability and Controlled Release of Si and Mg Bioactive Ions to Synergistically Promote Vascularized Bone Regeneration - Ling Wei; Zhiyun Du; Chenguang Zhang; Yingying Zhou; Fangyu Zhu; Yumin Chen; Han Zhao; Fengyi Zhang; Pengrui Dang; Yijun Wang; Yanze Meng; Boon Chin Heng; et al. (Advanced Materials Interfaces, 2023)
Abstract For bone defect repair, it is critical to utilize biomaterials with pro‐angiogenic properties to enhance osteogenesis. Hydroxyapatite (HA)‐based materials widely used in clinical applications have shown much potential for bone repair. However, their predominant calcium phosphate (CaP) composition and poor biodegradability limit their angiogenic potential and hence osteogenic efficiency of HA‐based materials. Here, a magnesium ion‐doped calcium silicate/HA composite microscaffold (Mg‐CS/HA) is fabricated to enhance angiogenesis and osteogenic efficiency for bone repair. Incorporation of CS improved the biodegradability of the Mg‐CS/HA microscaffold, which could simultaneously release Si and Mg bioactive ions during the early stage of implantation, synergistically enhancing angiogenesis and osteogenic efficiency. In co‐culture systems, the synergistic effects of Si and Mg ions promote the “osteogenesis‐angiogenesis coupling effect.” In vivo, the Mg‐CS/HA microscaffold could significantly promote reconstruction of the vascular network and bone regeneration. This study thus provides a new strategy for coordinated release of bioactive ions to achieve synergistic effects on vascularized bone regeneration by HA‐based bone implant materials.